Response of Lignin Metabolism to Light Quality in Wheat Population - Li, Chunhui; Luo, Yongli; Jin, Min; Sun, Shufang; Wang, Zhenlin; Li, Yong (Frontiers in Plant Science, 2021)
The low red/far-red (R/FR) light proportion at the base of the high-density wheat population leads to poor stem quality and increases lodging risk. We used Shannong 23 and Shannong 16 as the test materials. By setting three-light quality treatments: normal light (CK), red light (RL), and far-red light (FRL), we irradiated the base internodes of the stem with RL and FRL for 7h. Our results showed that RL irradiation enhanced stem quality, as revealed by increased breaking strength, stem diameter, wall thickness and, dry weight per unit length, and the total amount of lignin and related gene expression increased, at the same time. The composition of lignin subunits was related to the lodging resistance of wheat. The proportion of S+G subunits and H subunits played a key role in wheat lodging resistance. RL could increase the content of S subunits and G subunits and the proportion of S+G subunits, reduce the proportion of H subunits. We described here, to the best of our knowledge, the systematic study of the mechanism involved in the regulation of stem breaking strength by light quality, particularly the effect of light quality on lignin biosynthesis and its relationship with lodging resistance in wheat.